Discrepancies between general practitioners' vaccination recommendations for their patients and practices for their children. (May 2017) - Agrinier, N.; Le Maréchal, M.; Fressard, L.; Verger, P.; Pulcini, C.
Abstract: Objectives: The objectives of our study were to describe the vaccination recommendations by general practitioners (GPs) for their patients and practices for their children, and to identify any discrepancies between them. Methods: Applying multiple correspondence analysis and agglomerative hierarchical cluster analysis to data from a 2014 cross-sectional survey of a national sample of GPs, we constructed a typology based on the patterns of associations between GPs' vaccine recommendations to their patients and practices to their own children's vaccinations. Results: This study includes the 1038 GPs who reported that they had at least one child aged 2–25 years. Nearly half (47%, 482/1021) reported that all of their children were vaccinated against hepatitis B but that they did not always recommend that vaccine to patients; the same discordance was observed among 36% (369/1027) for the measles–mumps–rubella vaccine, 19% (194/1013) to 28% (290/1019) for routine and catch-up meningococcal C vaccination, and 27% (136/496) for the human papillomavirus vaccine. Cluster analysis showed that 37% (95% CI 33%–39%) of GPs reported an above-average rate of systematic vaccine recommendations for their patients, and most reported that all their children were vaccinated (low level of discordance), whereas 60% (95% CI 58%–64%) had a high level of discordance, that is, most reported that their children were vaccinated, but did not always recommend the same vaccines to their patients. Conclusions: Many GPs do not report the same attitude concerning the vaccination of their children and their patients. The reasons underlying these discrepancies, possibly including vaccine hesitancy, should be investigated.